Improve Basketball Shoothing Skills With The Target Method - Simamora, Hotlider H (CV Media Inti Teknologi, 2023)
The issue with pupils' precision while chucking the ball into the basketball hoop as well as their lack of interest and sincerity in studying is the basis of this study. The goal of this study was to enhance basketball shooting performance and raise student interest and motivation in target game basketball instruction. The collaborative and participatory nature of this study makes it a class action study. 35 kids from SMP Negeri 1 Rejang Lebong's VIII grade served as the study's subjects. Twelve male and twenty-three female students were present. After gathering the study data, it was examined using both quantitative and qualitative descriptive methods. The findings indicated that using target games in combination can raise student enthusiasm and seriousness about studying while also increasing basketball shooting accuracy. This is evident from the rise in student interest and seriousness as well as the improvement in basketball shooting outcomes, which allowed the second cycle's completion rate to reach 94.3%.